Penerapan Kurikulum Fungsional dalam Kemandirian Anak Penyandang Disabilitas Tunanetra di Yayasan Pendidikan Dwituna Harapan Baru Kota Medan - Vellin Syahya Jingga; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2023)
Education is important for children as a provision of knowledge in facing adult life. Children with visual impairments also need education as a preparation for adult life in the future, coupled with their limitations which require that the education they receive is not in the form of general learning activities, but has special methods and techniques so as that learning outcomes can be received optimally. Regardless, the learning activities of children with visual impairments involve independence as a learning accomplishment and focus on functional activities with the hope of increasing their motor,tactile, and auditory sensitivity. The functional curriculum exists as an educational service for children with visual impairments to improve their academic and motor skills, as well as build the child's independence. The purpose of this study was to find out how the implemented functional curriculum can increase independence in children with visual impairments at Yayasan Pendidikan Dwituna Harapan Baru Kota Medan. The research method used is a qualitative descriptive approach. Qualitative descriptive research is research that describes, explains, reveals and summarizes various existing conditions and situations from the results of research facts in the field. Data collection techniques were carried out by observing and interviewing. Based on the research that has been done, the results of the research show that the application of a functional curriculum is to provide learning based on the functions and benefits of learning activities given to blind children with independent characteristics at the Yayasan Pendidikan Dwituna Harapan Baru Kota Medan. Independence in the form of implementing functional curriculum learning is carried out using the Individual Education Program (IEP) model which is evaluated personally